An SSP‐PCR method for the rapid detection of disease‐associated alleles HLA‐A*29 and HLA‐B*51. (21st June 2018) - Amstutz, U.; Schaerer, D.; Andrey, G.; Wirthmueller, U.; Largiadèr, C. R.
Abstract : HLA‐A*29 and HLA‐B*51 are associated with birdshot uveitis and Behçet's disease, respectively, and are used as a diagnostic criterion in patients with suspected disease, requiring their detection in diagnostic laboratories. While commercial tests for individual HLA alleles are available for other disease‐associated HLA variants, no similar allele‐specific assays are available for HLA‐A*29 and HLA‐B*51. Here, we report sequence‐specific priming‐polymerase chain reaction (SSP‐PCR) methods for the detection of HLA‐A*29 and HLA‐B*51 using a single PCR reaction per allele. The assays were tested in 30 and 32 previously HLA‐typed samples, respectively, representing >97% of HLA‐A alleles and >93% of HLA‐B alleles in a European population. A concordance of 100% was observed with previous typing results, validating these methods for use in a diagnostic or research context.